Heat activation of Streptomyces viridochromogenes spores. - Hirsch, C F (1976)
The lag period preceding germination of Streptomyces viridochromogenes spores during incubation in a defined germination medium was completely eliminated by a gentle heat shock. The rate of germination was not affected. The optimum pH for activation extended from 6.0 to 9.6. The time of heating required for maximum activation was 1 min at 60 C, 2 to 5 min at 55 C, 20 min at 50 C, and 40 to 50 min at 45 C. Activated spores had the same temperature and pH optima and nutritional requirements for germination as unactivated spores. Activated spores deactivated during incubation for 8 h at 25 C and were activated again by a second heat shock. Spores that had been aged for 4 weeks or longer did not germinate in the defined germination medium unless they were first heat activated.